2005
DOI: 10.28945/486
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Myths about Online Education in Information Systems

Abstract: Rapid proliferation of the Internet along with emerging social and economic imperatives are leading institutions of higher-learning to offer a large variety of online courses/programs in different disciplines. As such education becomes increasingly pervasive and legitimate in society, there is a need to critically examine its merits and pitfalls as well as the underlying assumptions driving the justification, design, and teaching of online courses. In this paper, we take a first step in this direction by uncov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Of course, as online educators, we cannot assume that simply adding a new mode of communication will increase interaction. Such an argument reflects a powerful myth of online learning: that increased connectivity deterministically leads to increased interaction (Sarker & Nicholson, 2005). Yet, synchronous communication seems to set up a context within which interaction is likely to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, as online educators, we cannot assume that simply adding a new mode of communication will increase interaction. Such an argument reflects a powerful myth of online learning: that increased connectivity deterministically leads to increased interaction (Sarker & Nicholson, 2005). Yet, synchronous communication seems to set up a context within which interaction is likely to increase.…”
Section: Discussionmentioning
confidence: 99%
“…For as long as there have been "distant" modes of learning, research has been conducted to examine if it is as good as "traditional" methods of delivery. While some studies find differences in effectiveness when comparing IT-mediated and traditional face-to-face learning environments, many studies indicate that there are no significant differences (Russell, 1999;Sarker & Nicholson, 2005). We believe that it is time to investigate more systematically what makes technology-mediated learning environments different (more effective in some circumstances, while less effective in others), rather than simply trying to emulate the face-to-face experience in an online environment.…”
Section: Course Suitability In Technology-mediated Learning (Tml) Envmentioning
confidence: 99%
“…As suggested by Piccoli, Ahmad and Ives (2001, p. 408), "Considerable uncertainty remains regarding the subject matter and content type best suited to delivery in the virtual environment". In their exploratory analysis of the "myth' that any course can be taught online, Sarker and Nicholson (2005) found that both instructors and students indicated that certain kinds of courses were more (or less) suitable for online delivery. For example, some students stated: "I personally find it difficult to learn math, programming, and high-logic based courses this way.…”
Section: Teaching Effectiveness In Tml Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this fact, opinions on the subject that are nearly polar opposites persist (e.g., Hirshheim, 2005;Gill, 2006) and myths abound (Sarker & Nicholson, 2005). One likely explanation for the lack of consensus is that the establishment of distance learning programs invariably involves the interaction between disciplinary and institutional informing systems.…”
Section: Distance Learning Educators and Administratorsmentioning
confidence: 99%